EU competition policy enforcement supports investment in the energy sectors - Tomaso Duso; Jo Seldeslachts; Florian Szücs (DIW Economic Bulletin, 2016)
Energy sectors-primarily power generation and gas production, but also energy transmission and distribution-require significant capital investment in infrastructure. Market structures as well as the degree of competition and regulation are key factors that determine firms' incentive to invest. Yet the empirical research on the link between these factors and private investment is still quite scarce, especially in the energy sectors. In this study, we empirically examine whether competition policy enforcement and regulatory intervention in European gas and electricity markets affects firms' incentive to invest. Our findings show that EU merger policy enforcement is significantly related to a higher investment in low-regulated markets.
Keywords: D24; L4; L98; Q4; 330; Investment; Energy; Competition; Competition Policy; Regulation